Barriers to Industrial Advancement for Women in Idoma Rural Areas: A Sociological Study - Olowu, Josephine (Kashere Journal of Politics and International Relations, 2025)
The industrial advancement of women, particularly in rural areas, remains a critical determinant of socio-economic growth and gender equity. This study examines the barriers hindering industrial progression among women in Idoma rural communities, Benue State, Nigeria. Employing a qualitative approach, the study explores cultural, educational, financial, infrastructural, and institutional impediments through in-depth interviews and focus group discussions. Findings reveal that patriarchal cultural practices, low educational attainment, limited access to credit facilities, poor infrastructure, and weak policy implementation significantly restrict women's industrial participation and success. The study recommends targeted policy interventions, improved access to education, financial empowerment programs, and the dismantling of cultural norms that inhibit women's advancement. This research contributes to the growing sociological discourse on gender inequality and rural industrialization.